Dental fluorosis in a sample of adolescents from the state of Coahuila, Mexico - Estrada Valenzuela, Cristian Mayela; Llodra Calvo, Juan Carlos (Acta Universitaria, 2019)
Dental fluorosis is a pathology for which little information about its prevalence in the state of Coahuila, Mexico is available. The aim of this descriptive study with transverse temporality is to identify the dental fluorosis prevalence and severity on adolescents aged 12 and 15 years. A questionnaire, a modified Dean’s fluorosis index, and a community’s fluorosis index were used to examine the upper anterior sextant of 1205 adolescents. The total prevalence of fluorosis for Coahuila was calculated in 53%. According to the severity index, the most prevalent code was very mild. The community’s fluorosis index was 0.602, this value indicates closeness to a public health problem. It is suggested to investigate water wells of the involved communities, in order to avoid a public health issue.